Fenomena Keberagamaan di Media Sosial; Deskripsi Analasis Wacana Seni dan Budaya di Media Sosial - Syaiful Halim; Ahmad Rifai; Ace Somantri (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The phenomenon of religiosity from social settings begins to move into the cyber realm. The dialectic of religious understanding based on belief appears in the digital realm. arguments and different opinions and even mocking each other also occurs in the cyber realm. Social media is a gathering place for the Islamic community to show religious understanding in the form of statements, images, and symbols. This study uses a qualitative approach to describe the pattern of religious communication on social media. The results of the study show that theological elements are carried over to the realm of communication on social media. Differences of opinion regarding art and culture are haram or not keep popping up. At first they mocked each other between netizens, then it led to a theological dialogue that fell between infidel or non-infidel. Therefore, practical instructions from religious authorities are needed to provide alternative solutions to netizens, so that there is no mutual disapproval on social media. Keywords : social media, religious understanding, art and culture.